Kelimpahan Kopepoda (Copepods) sebagai Stok Pakan Alami di Perairan Desa Pengudang, Bintan - Tengku Said Raza'i; Imam Pangestiansyah Putra; M. Aris Suhud; Muhammad Firdaus (Intek Akuakultur, 2018)
Copepods is one of the important elements in the food chain in aquatic ecosystems. Its role in the food chain for energy transfer from producers to first-level consumers, namely as food for small fish in the larval phase. Observations were made by purposive sampling at 3 research stations (river estuary area, fishing area, and residential area). 7 species of copepods were identified including Callanus sp., Lucicutia sp., Macrosetella sp., Nauplius sp., Oithona sp., Rhincalanus sp., Scolecithricella sp. The abundance of copepods in Pengudang Village waters is an average of 188.14 ind/L. Of the 7 types of copepods found, types of copepods were Callanus sp., Macrosetella sp., Nauplius sp., Oithona sp., Rhincalanus sp., and Scolecithricella sp. which has generally been developed for use as natural food.